Effectiveness of oral itraconazole in the management of otomycosis with tympanic membrane perforation - Ravindran, Aju; M., Sagesh (International Journal of Research in Medical Sciences, 2017)
Background: Otomycosis can be a difficult problem to treat in a patient who already has a perforation of the tympanic membrane. This study highlights the effectiveness of oral Itraconazole in treating such cases. Methods: Thirty-four patients with otomycosis and a perforated tympanic membrane were included in the study and were treated with oral itraconazole and antibiotic ear drops. They were followed up for six weeks to look for treatment response and any recurrence. Results: Of the 34 patients in the study, 25 patients were fully cured with one week of oral Itraconazole therapy. Six out of the remaining 9 patients were cured of the disease with two weeks’ therapy. Three patients needed prolonged treatment and one patient had a recurrence at six weeks. Conclusions: Oral itraconazole therapy is an effective alternative to the traditional methods of treatment for otomycosis with tympanic membrane perforation.